The Term "can" In General & Special Criminal Offenses Based on Principles, Theories, and Criminal Law Doctrines - Youngky Fernando (Law Doctoral Community Service Journal, 2023)
The term “can” is a legal term often used in relation to general offenses and specific offenses in criminal law. In the context of general offenses, the term “can” refer to the authority or power delegated to authorized officials to take criminal actions. The purpose of this study is to discuss the phrase “can” in general and specific offenses based on principles, theories, and doctrines of criminal law. The research method used is normative legal research, utilizing primary, secondary, and tertiary legal materials, through a legislative approach.